RANCANG BANGUN MESIN PASCA PANEN HANJELI - Asep Yusuf; Ahmad Thoriq; Zaida Zaida; Asri Widyasanti; Ganjar Dianugraha Alam (Jurnal Ilmiah Rekayasa Pertanian dan Biosistem, 2019)
Food needs will continuous to increase along with population growth rate continuous to rise, so is needed the alternative foodstuff to be developed, one of is job’s tears. Before job’s tears is processed there are many process are shelling, polishing of aleuron layer, separating of job’s tears from bran, and milling.Job’s tears utilization as food as still constrained in shelling the outer leather because the leather is very hard, so is neededthe design of job’s tears shelling machine for easy in shelling before polishing. The research was conducted in July - November 2018 on Repair Laboratory Metal Wood and Rattan, Faculty ofAgro-Industrial Technology, Padjadjaran University.Research use engineering methode by doing an design activity. The result is a job’s tears post-harvest machine including sheller unit, separator unit, and polisher unit with the main components are framework, transmission system, hopper, sheller cylinder and output. This machine can use for shelling of stones job’s tears with none shelled job’s tears <35%.